2021
DOI: 10.1007/s10260-021-00563-9
|View full text |Cite
|
Sign up to set email alerts
|

Studying the relationship between anxiety and school achievement: evidence from PISA data

Abstract: Using the Programme for International Student Assessment (PISA) 2015 data for Italy, this paper offers a complete overview of the relationship between test anxiety and school performance by studying how anxiety affects the performance of students along the overall conditional distribution of mathematics, literature and science scores. We aim to indirectly measure whether higher goals increase test anxiety, starting from the hypothesis that high-skilled students generally set themselves high goals. We use an M-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…These findings supported H2 and H3. Class competition negatively affected students’ academic achievement by increasing their learning anxiety, which was consistent with conclusions drawn by Sariem et al (2014) and D’Agostino et al (2021) . According to Lewin’s field theory ( Lewin, 1936 ), individuals’ mental activity and behaviors are closely related with the environment they live.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings supported H2 and H3. Class competition negatively affected students’ academic achievement by increasing their learning anxiety, which was consistent with conclusions drawn by Sariem et al (2014) and D’Agostino et al (2021) . According to Lewin’s field theory ( Lewin, 1936 ), individuals’ mental activity and behaviors are closely related with the environment they live.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies confirmed that learning anxiety can lead to poor academic achievement among students (Sariem et al, 2014;Chang and Beilock, 2016;D'Agostino et al, 2021). Emotions have been found to affect a wide range of cognitive processes, including attention, memory storage and retrieval, social judgment, decision making and cognitive problem solving (Clore and Huntsinger, 2009).…”
Section: Mediating Role Of Learning Anxietymentioning
confidence: 91%
“…These findings supported H2 and H3. Class competition negatively affected students' academic achievement by increasing their learning anxiety, which was consistent with conclusions drawn by Sariem et al (2014) andD'Agostino et al (2021). According to Lewin's field theory (Lewin, 1936), individuals' mental activity and behaviors are closely related with the environment they live.…”
Section: Mediating Roles Of Learning Anxiety and Learning Engagementsupporting
confidence: 82%
“…He demonstrated that children with lower academic self-concepts showed higher anxiety levels, with anxiety negatively predicting future achievements [ 26 ]. Likewise, other authors have also suggested the need to study the negative effects of anxiety on school performance [ 27 ] since students with higher anxiety levels are likely to learn less [ 28 ]. However, the association between happiness and academic performance is an emerging area of research, and, unfortunately, there is limited evidence on this relationship in children and adolescents [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%